Does Class Size Matter? A Reassessment of the Moderating Role of Class Size on the Effectiveness of E-Learning in Arabic Language Acquisition - Abdullah, Muhammad Yahya; Putri, Amanda; Ufairah, Nabila Izzatul; Amal, Muhammad Ikhlasul; Sesfao, Djiki Yuinggris (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study investigates the effect of e-learning on Arabic language learning outcomes, with a particular focus on how class size moderates this relationship. Despite the growing use of e-learning in education, the impact of class size on its effectiveness remains unclear. The objective of this study is to assess the effect size of e-learning on Arabic language learning across different class sizes and to explore the moderating role of class size in this relationship. Using a meta-analysis approach, data from 21 studies were analyzed with OpenMee Software. The results show that e-learning has a significant positive effect on Arabic language learning, with a larger effect observed in larger classes compared to smaller ones. Specifically, larger classes are found to provide more opportunities for interaction, which enhances student engagement and learning outcomes. These findings challenge the traditional belief that smaller classes are inherently more effective. The study highlights the importance of class size as a moderating variable in the effectiveness of e-learning and provides valuable insights into how e-learning strategies can be optimized for different class sizes. However, the study is limited by the focus on Arabic language learning and the small number of studies analyzed. Future research should explore the impact of e-learning in other subject areas and conduct longitudinal studies to assess the long-term effects of e-learning on language learning outcomes.